Comparison of four sections for analyzing running mechanics alterations during repeated treadmill sprints - Girard, O.; Brocherie, F.; Morin, J.-B.; Degache, F.; Millet, G. P. (Journal of Applied Biomechanics, 2015)
We compared different approaches to analyze running mechanics alterations during repeated treadmill sprints. Thirteen active male athletes performed five 5-second sprints with 25 seconds of recovery on an instrumented treadmill. This approach allowed continuous measurement of running kinetics/kinematics and calculation of vertical and leg stiffness variables that were subsequently averaged over 3 distinct sections of the 5-second sprint (steps 2-5, 7-10, and 12-15) and for all steps (steps 2-15). Independently from the analyzed section, propulsive power and step frequency decreased with fatigue, while contact time and step length increased (P < .05). Except for step frequency, all mechanical variables varied (P < .05) across sprint sections. The only parameters that highly depend on running velocity (propulsive power and vertical stiffness) showed a significant interaction (P < .05) between the analyzed sections, with smaller magnitude of fatigue-induced change observed for steps 2-5. Considering all steps or only a few steps during early, middle, or late phases of 5-second sprints provides similar mechanical outcomes during repeated treadmill sprinting, although acceleration induces noticeable differences between the sections studied. Furthermore, quantifying mechanical alterations from the early acceleration phase may not be readily detectable, and is not recommended.